Head-Neck Motion in Prehospital Trauma Patients under Spinal Motion Restriction: A Pilot Study. (2nd January 2021) - McDonald, Neil; Kriellaars, Dean; Weldon, Erin; Pryce, Rob
Abstract: Background: Spinal precautions are intended to limit motion of potentially unstable spinal segments. The efficacy of various treatment approaches for motion restriction in the cervical spine has been rigorously investigated using healthy volunteers and, to a lesser extent, cadaver samples. No previous studies have objectively measured this motion in trauma patients with potential spine injuries during prehospital care. Objective: The purpose of this study was to characterize head-neck (H-N) kinematics in a sample of trauma patients receiving spinal precautions in the field. Methods: This was a prospective observational study of trauma patients in the prehospital setting. Trauma patients meeting criteria for spinal precautions were eligible for inclusion. Participants received usual care, consisting of either a long backboard, cervical collar, and head blocks (BC) or a cervical collar only (CO), and behavior was categorized as compliant (C) or non-compliant (N). Three inertial measurement units (IMUs), placed on each participant's forehead, sternum, and stretcher, yielded data on H-N motion. Outcomes were described in terms of H-N displacement and acceleration, including single- and multi-planar values, root mean square (RMS), and bouts of continuous motion above pre-determined thresholds. Data were analyzed to compare H-N motion by phase of prehospital care, as well as treatment type and patient behavior. Results: Substantial single- and multi-plane H-N motion was observed among all participants. Maximum single-plane displacements were between 11.3 ± 3.0 degrees (rotation) and 19.0 ± 16.6 degrees (flexion-extension). Maximum multi-plane displacements averaged 31.2 ± 7.2 degrees (range: 7.2 to 82.1 degrees). Maximum multi-plane acceleration averaged 5.8 ± 1.4 m/s 2 (range: 1.2 to 19.9 m/s 2 ). There were no significant differences among participants between prehospital phase and treatment type. Non-compliant participants showed significantly more motion than compliant participants. Conclusion: Among actual patients, movement appears to be greater than previously recorded in simulation studies, and to be associated with patient behavior. Miniature IMUs are a feasible approach to field-based measurement of H-N kinematics in trauma patients. Future research should evaluate the effects of patient compliance, treatment, and phase of care using larger samples. Key words: spinal immobilization; cervical spine; cervical collar; long backboard